âEnergy devices in gynecological laparoscopy â Archaic to modern eraâ - Amruta Jaiswal; Kuan-Gen Huang (Wolters Kluwer Medknow Publications, 2017)
The introduction of newer vessel sealing systems has revolutionized techniques of hemostasis during laparoscopic surgery. These devices allow for rapid sequential tissue and vessel sealing, coagulation, and transection. Despite of widespread use of newer advanced bipolar and ultrasonic devices, monopolar and conventional bipolar electro-surgery still carry weightage due to wider range of tissue effect, dissection capabilities, cost effectiveness, and ease of availability. Here in we discussed different types of commonly available energy sources in terms of mechanism, efficacy and safety as thorough knowledge is utmost important for surgeon to choose appropriate instrument for surgical procedure. Keywords: Electrosurgery, Energy devices, Gynecology, Laparoscopy